Da prædikebrødrene kom til Holbæk: Om de mulige bevæggrunde og samtidspolitiske forhold bag en dominikansk klosterstiftelse på Sjælland i starten af senmiddelalderen - Jakobsen, Johnny Grandjean Gøgsig (Kirkehistoriske Samlinger, 2003)
The Friars Preachers - or »Black Friars« - came to Holbæk in the year 1269 or 1275, where they were given some land on the south side of the small town, probably by the king. In 1276, Bishop Peter Bang of Roskilde consecrated a churchyard for the brethren. The friars did not get an easy start in Holbæk, as a chronicle from Roskilde tells us, that in 1287 »the house of the friars burned down together with the entire city of Holbæk«. In the early 1290s, the outlawed Marshal Stig and his followers ravaged the town. Not all events in these years were bad, though, as the documents tell us about donations of money in 1292 and 1307 by two noblewomen. Finally, in 1323, Bishop Niels of Børglum could consecrate a church of the Friars Preachers of Holbæk, presumably built by financial support from King Christopher II. Basically, these few data are all we know about the foundation of the Dominican convent in Holbæk. Unfortunately, this is only too representative for mendicant convents in Denmark. Because of this, scholars often seek to rather traditional and superficial explanations, when they - if at all -try to describe the reasons and background for the Dominican and Franciscan foundations. The mendicant orders of the 13th century are usually seen as a reformist reaction of the Catholic Church against heretics and a growing dissatisfaction with the secular clergy among the population in the towns. I am in no way claiming, that this tradition is wrong, but it is my conviction, that the true explanation is much more complex - and often more individually based for each convent. Even though, the written sources of the Dominican foundation in Holbæk as well as in most other Danish towns are very scarce, I believe, that it is possible to give a broader picture of the ideas and interests behind the actions - especially if we bring in sources and studies from our neighbouring countries. In this article, I have tried to describe some ofthe possible reasonings behind the foundation in Holbæk. For the citizens of the young town, it was of vital importance to maintain and strengthen the status of the town, which the foundation of a mendicant convent seems to have been a widely used way of doing. The mere existence of the friars was a sign of urban importance. By having a mendicant convent and - later on - a mendicant church, the townspeople also became less dependant upon the secular church, represented by the parish churches, which were controlled by the bishop and the canons of Roskilde. Moreover, it should not be ignored, that the priory in Holbæk was founded right after (or during) one of the big strives between the Crown and the Church of Denmark. During the fight between King Christopher I. and Archbishop Jakob Erlandsen (and, which is quite important for Zealand, his nephew Bishop Peter of Roskilde), the Order of Preachers in Scandinavia sided with the king, both by representing the royal interests in the papal court, and by ignoring the interdict called upon the kingdom by first the archbishop and the bishop, and later on by the pope. As Holbæk with its royal »castle« can be considered a royal stronghold on Zealand, it would certainly be in the King’s interest to reduce the episcopal influence in the town, which the foundation of a Dominican convent must have seemed an obvious way of doing by that time. Even the overall international situation of the Dominican Order may have played a role in the Holbæk foundation. The mendicant orders had experienced a significant and growing opposition from both the secular church and the intellectual milieu at the universities from the middle of the 13th century. In 1269, another major attack against the Dominicans and the Franciscans had risen, and even though the orders were able to ride off the storm, it must have been obvious to the brethren, that their privileges could no longer be taken for granted. An actual stop for more foundations of convents was not at all unrealistic, so it was in the interest of the orders, to implement all planned and potential foundations while it was still possible. When the papal move against the mendicants finally came in 1300 with the Super Cathedram, it did not mean the end of the friars or more convents, but it did put an end to their former highly privileged position towards the secular church. For instance, when the papal bull was finally implemented in 1311, the friars could no longer use the parish churches for preaching and celebrating masses without the consent of the local priests - who in Holbæk were serving directly under the canons of Roskilde. In the dispute of later scholars in Holbæk on whether the church of 1323 replaced an older Dominican church or not, this papal decision against the right of friars to preach in the local churches could in my opinion support the idea, that the church built in the early 1320s, also indeed was the first. Only too often, we treat the Middle Ages as a static and rather homogeneous period. Nothing could be more wrong. The actual time of the arrival of the Friars Preachers in Holbæk in the 1260-70s, and the later consecration of the priory church in 1323, must be taken into consideration, as both these events took place in a completely different political environment than, for instance, the earlier establishing of a Dominican convent in the episcopal centre of Roskilde, or the much later foundation in Ellsinore. The foundations of Dominican convents happened in different cities at different times, and even though we should try to identify all common features of these foundations, if we are to broaden our understanding of them, we must also be aware, that the political climate of the medieval world -just like today - could change dramatically from one generation to another. And the Friars Preachers, just like everyone else, had to adapt and adjust to the given conditions of their time and local environment.